Environment - Reed, Catherine, 1950- (Vero Beach, Fla. : Rourke Publications, 1992)
Text and photographs explain the scientific method with suggests various projects related to the environment.
Includes index and glossary.
Book Report.
6.1.
6.1
3-6.
3-6
Keywords: Ecology -- Experiments -- Juvenile literature; Environmental engineering -- Experiments -- Juvenile literature; Human ecology -- Experiments -- Juvenile literature; Science projects -- Juvenile literature; Ecology -- Experiments; Environmental engineering -- Experiments; Experiments; Human ecology -- Experiments; Science projects; Ecology -- Experiments; Human ecology -- Experiments; Science -- Experiments